Endothelial cells present an innate resistance to glucocorticoid treatment: implications for therapy of primary vasculitis. Issue 5 (27th December 2011) - Koenen, Paola; Barczyk, Katarzyna; Wolf, Marc; Roth, Johannes; Viemann, Dorothee
Abstract : Background: In contrast to other chronic inflammatory diseases glucocorticoids alone do not maintain sufficient remission in primary vasculitis. The reasons for this therapeutic failure remain unclear. Objectives: To investigate the molecular effects glucocorticoids exert on endothelial cells (EC) and to elucidate the molecular pathways responsible. Methods: A comparative approach was used to treat human micro and macrovascular EC as well as monocytes long and short term with glucocorticoids or glucocorticoids and tumour necrosis factor alpha (TNFα). Gene expression changes were analysed applying microarray technology, sophisticated bioinformatic work-up and quantitative reverse transcription PCR. Glucocorticoid receptor translocation processes were traced by cell fractionation assays and immunofluorescence microscopy. Results: In EC glucocorticoids completely failed to inhibit the expression of immune response genes both after sole glucocorticoid exposure and glucocorticoid treatment of a TNFα-induced proinflammatory response. In contrast, an impressive downregulation of proinflammatory genes was seen in monocytes. The study demonstrated that the glucocorticoid receptor is comparably expressed in EC and monocytes, and demonstrated good translocation of ligand-bound glucocorticoid receptor allowing genomic glucocorticoid actions. Refined gene expression analysis showed that in EC transactivation takes place and causes glucocorticoid side effects on growth and metabolism whereas transrepression-mediated anti-inflammatory effects as in monocytes are missing. Insufficient induction of SAP30, an important constituent of the Sin3A-histone deacetylase complex, in EC suggests impairment of transrepression due to co-repressor absence. Conclusions: The impressive unresponsiveness of EC to anti-inflammatory glucocorticoid effects is associated with deficiencies downstream of glucocorticoid receptor translocation not affecting transactivation but transrepression. The findings provide the first molecular clues to the poor benefit of glucocorticoid treatment in patients with primary vasculitis.